RELEVANSI KONSEP PERPAJAKAN MENURUT ABU YUSUF DAN IBNU KHALDUN TERHADAP PEREKONOMIAN DI INDONESIA - Misbahul Ali (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2021)
Tax is one of the most important instruments in the development of a country. This is because the development budget and government operations have a heavy dependence on taxes. However, at this time, the ratio of tax revenue in Indonesia is relatively small. This of course will have a bad impact on the country's development, given the expenditure budget whose contribution ratio is getting bigger. The lack of tax revenue is caused by a lack of public awareness in paying taxes and the rampant corrupt practices that exist in this country. Abu Yusuf and Ibn Khaldun with their intellect which is based on Islamic teachings by considering mashlahah and justice, managed to come up with tax theories that are relevant to the economy in Indonesia today. There are several tax theories according to Abu Yusuf and Ibn Khaldun which are considered relevant and can be a solution for the economy in Indonesia. Among them, the muqasamah system if applied today is still very relevant, especially the self-assessment system currently in effect in Indonesia that allows taxpayers to cheat. The Usyur that was in effect at the time of Abu Yusuf if it is relevant to the present, has several similarities with the collection of customs taxes